ZOONOTIC HOOKWORM THAT POTENTIALLY CAUSES CREEPING ERUPTION IN CAKRANEGARA - Resnhaleksmana, Ersandhi; Ariami, Pancawati; Danuyanti, I Gusti Ayu Nyoman (Jurnal Analis Medika Biosains (JAMBS), 2014)
AbstractMaintenance of animals like dogs in Cakranegara not matched with a good understanding of the spread of the disease. That Causes increase the risk of disease transmission from animal to animal or from animal to human. A wild dog that lives at risk of disease transmission is higher than the breed. One of the animal diseases that can be transmitted to humans (zoonoses) is a Hookworm. which can cause creeping eruption. This study was an observational descriptive, with the aim to determine the prevalence of Zoonotic Hookworm in dogs that could potentially cause creeping eruption in Cakranegara. Sampling was purposive sampling as many as 30 samples with wet paint (direct) and Berrman methods. Results, the prevalence of zoonotic hook worm was 14 of 30 samples of dog feces (46%).Keywords: Prevalence, Zoonotic Hookworm, Creeping eruption.